1988
DOI: 10.1200/jco.1988.6.10.1625
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for brain metastases.

Abstract: We report the results of reoperation for brain metastases in 21 patients with recurrent tumors following initial successful resection. The tumor recurrences were local (original site) in 14 patients, and occurred at other sites in the brain in the remaining seven. Time to CNS recurrence ranged from 3 to 30 months. At time of repeat craniotomy, disease was limited to the CNS in 12 (57%) of the patients. Median survival following second craniotomy was 9 months, and the actuarial 2-year survival was 25%. Neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 20 publications
3
14
0
1
Order By: Relevance
“…Anderson. The data from this article confirmed those of Sundaresan et al [34] in that the median survival time after resection was 11.5 months, with 2-year and 5-year survival rates of 26% and 17%, respectively. No operative morbidity or mortality occurred.…”
Section: Recurrent Brain Metastasessupporting
confidence: 93%
See 1 more Smart Citation
“…Anderson. The data from this article confirmed those of Sundaresan et al [34] in that the median survival time after resection was 11.5 months, with 2-year and 5-year survival rates of 26% and 17%, respectively. No operative morbidity or mortality occurred.…”
Section: Recurrent Brain Metastasessupporting
confidence: 93%
“…According to the first such report, by Sundaresan et al [34] in 1988, 21 patients originally treated with surgery for single brain metastases underwent repeat craniotomy for the recurrent lesion. These patients survived for a median of 9 months after the second surgery, and 24% of patients survived for more than 2 years.…”
Section: Recurrent Brain Metastasesmentioning
confidence: 99%
“…Past studies have shown that repeat NS in select patients can result in neurologic improvement with minimal morbidity and mortality as reported here [12]. Local recurrence after resection can occur in up to 46% of cases [13].…”
Section: Treatment Of Brain Metastasis In Breast Cancersupporting
confidence: 60%
“…Surgical resection may have a role in selected patients with symptomatic recurrent lesions. Patients with good performance status, controlled systemic disease, and a long interval after initial resection are most likely to benefit from reoperation [33][34][35]. Cost effectiveness The cost of a craniotomy is approximately $10,000 to $20,000, whereas that for a stereotactic biopsy is $7,000 to $12,000.…”
Section: Surgerymentioning
confidence: 99%